2017
DOI: 10.1080/10408398.2017.1406332
|View full text |Cite
|
Sign up to set email alerts
|

Trace minerals intake: Risks and benefits for cardiovascular health

Abstract: Minerals play a major role in regulating cardiovascular function. Imbalances in electrolyte minerals are frequent and potentially hazardous occurrences that may lead to the development of cardiovascular diseases (CVDs). Transition metals, such as iron, zinc, copper and selenium, play a major role in cell metabolism. However, there is controversy over the effects of dietary and supplemental intake of these metals on cardiovascular risk factors and events. Since their pro-oxidant or antioxidant functions can hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 150 publications
2
70
2
3
Order By: Relevance
“…Also, there seem to be no clear mortality benefits from moderate alcohol intake, although wine might have a distinct effect because it rarely entails binge drinking [30,31]. Moreover, increased adherence to the SEAD was correlated in our study with a nutrient pattern that has been linked to lower risk of death: (1) decreased saturated fat and increased omega-3 fatty acid intakes [32,33], (2) increased protein intake (although its effects on mortality could be opposite in older and younger subjects) [34][35][36], (3) increased fiber intake [37], and (4) increased vitamin and mineral intake (but not of sodium) [38][39][40][41].…”
Section: Discussionsupporting
confidence: 53%
“…Also, there seem to be no clear mortality benefits from moderate alcohol intake, although wine might have a distinct effect because it rarely entails binge drinking [30,31]. Moreover, increased adherence to the SEAD was correlated in our study with a nutrient pattern that has been linked to lower risk of death: (1) decreased saturated fat and increased omega-3 fatty acid intakes [32,33], (2) increased protein intake (although its effects on mortality could be opposite in older and younger subjects) [34][35][36], (3) increased fiber intake [37], and (4) increased vitamin and mineral intake (but not of sodium) [38][39][40][41].…”
Section: Discussionsupporting
confidence: 53%
“…Thus, appropriate intake of nutritional determinants and maintaining their reasonable levels play important roles in controlling stroke risk. Although accumulating evidence has indicated that trace elements might exert effects on stroke [ 9 , 10 ], there is still limited evidence of dietary supplementation for stroke prevention [ 11 ], suggesting that much more evidence is needed to clarify this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Ці мінеральні речовини мають високу біологічну активність, містяться у продуктах харчування, питній воді, тканинах людини та тварини. Мідь, кобальт, цинк, марганець, залізо беруть участь майже в усіх біологічних процесах, що відбуваються у тканинах організму, та мають досить специфічну дію (Ekici et al, 2004;Mohammadifard et al, 2017). Мідь виступає необхідним компонентом дихального ферменту цитохромоксидази.…”
Section: вступunclassified